Maternal Circulating Concentrations of Tumor Necrosis Factor-Alpha, Leptin, and Adiponectin in Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis - Jie Xu; Yan Hong Zhao; Yun Ping Chen; Xiao Lei Yuan; Jiao Wang; Hui Zhu; Chun Mei Lu (The Scientific World Journal)
Gestational diabetes mellitus (GDM) is one of the most common pregnancy complications. Inflammation may play a role in the pathogenesis of GDM. We performed a systematic review and meta-analysis to determine whether maternal serum concentration of tumor necrosis factor-alpha (TNF-α), leptin, and adiponectin were associated with GDM. A systematic search of PubMed and Medline was undertaken. In total, 27 trials were evaluated by meta-analyses using the software Review Manager 5.0. The results showed that maternal TNF-α (P=0.0003) and leptin (P<0.00001) concentrations were significantly higher in GDM patients versus controls. However, maternal adiponectin (P<0.00001) concentration was significantly lower in GDM patients compared with controls. Subgroup analysis taking in consideration the effect of obesity on maternal adipokine levels showed that circulating levels of TNF-α and leptin remained elevated in GDM patients compared to their body mass index (BMI) matched controls, and adiponectin level remained depressed in GDM individuals. Our findings strengthen the clinical evidence that GDM is accompanied by exaggerated inflammatory responses.